2000
DOI: 10.4141/p99-064
|View full text |Cite
|
Sign up to set email alerts
|

The influence of harvest management and fertilizers on herbage yields of cool-season grasses grown in the Aspen Parkland of northeastern Saskatchewan

Abstract: . 2000. The influence of harvest management and fertilizers on herbage yields of cool-season grasses grown in the Aspen Parkland of northeastern Saskatchewan. Can. J. Plant Sci. 80: 747-753. This study was conducted to evaluate the impact of harvest and fertilizer management on the herbage yield of various grass cultivars grown in the Aspen Parkland region of northeastern Saskatchewan. A series of three experiments were set out: site 1 at Pathlow, Gray Luvisolic soil, 1980; site 2 at Melfort, Deep Black Cherno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…These results are similar to those reported by Fairey (1991), Simons (1996, 1998) and Bittman et al (2000). There was a significant fertilizer × harvest interac- For personal use only.…”
Section: Protein Concentration In Herbagesupporting
confidence: 90%
See 2 more Smart Citations
“…These results are similar to those reported by Fairey (1991), Simons (1996, 1998) and Bittman et al (2000). There was a significant fertilizer × harvest interac- For personal use only.…”
Section: Protein Concentration In Herbagesupporting
confidence: 90%
“…Thus, there is a need to evaluate the response of pastures to nutrients. McCaughey and Simons (1996) and Bittman et al (2000) showed that frequent harvesting often reduces the yield response to applied N. There was, similarly, a tendency for N use efficiency and recovery of fertilizer N to be somewhat lower for multi-cut than for hay management, although in a study by McCaughey and Simons (1998), there did not appear to be any more nitrate-N left in the soil of the frequently cut grass plots than hay-cut plots in autumn. In contrast, herbage N concentrations were generally higher under frequent harvest, because the plants were less mature at harvest, whereas the total N offtake could be higher or lower with frequent harvesting depending on species, soil, and year (Fairey 1991;Simons 1996, 1998).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Root growth is suppressed by defoliation in non-native grasses including crested wheatgrass (Richards 1984). Defoliation also decreases aboveground biomass yield, but conversely increases late season growth (McCaughey and Simons 1998;Bittman et al 2000). Seed production is also decreased by defoliation (Hansen and Wilson 2006).…”
Section: Restoration and Managementmentioning
confidence: 99%
“…In eastern Nebraska and central Iowa, smooth bromegrass had equal to or greater yield than intermediate wheatgrass (23,24). Smooth bromegrass tends to have greater yield than the other bromegrass species (6,16); however, under irrigation meadow bromegrass yielded more than smooth bromegrass in western Canada (27). The yield of timothy was lower than intermediate wheatgrass but was not different from the three bromegrass species (Table 1).…”
Section: Yieldmentioning
confidence: 99%